Effects of desulfurized gypsum on shrinkage behavior of alkali-activated slag (AAS) and hybrid alkali-activated cement (HAC) - Lili Xue; Zhenkun Ni; Zhengning Zhou; Zuhua Zhang; Houren Xiong; Hao Wang; Xifeng Zhuge; Hongfei Liu (Case Studies in Construction Materials)
This study reports the use of desulfurized gypsum (DSG) to mitigate the shrinkage problem of two typical alkali-activated materials (AAMs), i.e. alkali-activated slag (AAS) and hybrid alkali-activated cement (HAC). The effects of DSG type and content on the hydration kinetics, mechanical properties, autogenous/drying shrinkage, and microstructure evolution of the AAMs were investigated. Results indicate that DSG can retard the hydration process and reduce the formation of gel products. Incorporating DSG into AAM mortar leads to a reduction in both autogenous and drying shrinkage, showing better efficiency than normal gypsum. An insights into the mechanisms underlying shrinkage for the DSG-AAM systems was gained through MIP, 1H NMR,XRD,TG-DTG, and SEM-EDS analyses. It was discovered that the higher Ca/Si of gel (amorphous C-A-S-H) phase and the higher crystalline/gel phases ratio in the DSG-AAM systems contributed to mitigating drying shrinkage. In addition, the shift of gel pore and capillary pore size and distribution contribute the reduced shrinkage.